Holonic Execution: A BDI Approach - Jarvis, Jacqueline; Jarvis, Dennis; Rönnquist, Ralph (Studies in Computational Intelligence, 2008)
Holonic manufacturing has been an active area of research for the past decade. However, this work has been predominately in the areas of planning and scheduling on the one hand and control on the other. In this book we propose these two areas can be integrated through adopting a focus on execution. In developing a conceptual model for holonic manufacturing execution, we draw together research threads from both holonics (the notion of a holon being both a whole in itself and part of a larger system) and multi-agent systems (the modelling of behaviour in terms of Beliefs, Desires and Intentions). The resulting model is mapped to two different BDI frameworks and then used to develop two separate execution systems for an industrial strength robotic assembly cell. As such, the book will be of interest to both researchers and practitioners in the holonic systems, manufacturing systems and multi-agent systems communities. It will also be of interest to the wider complex systems community, as it introduces what may become a new paradigm for complex systems development in the form of Team Programming.